Typification of Celtis (Cannabaceae) names described for Argentina, Bolivia, and Paraguay - Zamengo, Henrique B. (2023)
During the preparation of the treatment of the genus Celtis for the Neotropical region, some names from Argentina, Bolivia, and Paraguay were found in need of typification. In this context lectotypes are designated for six names (Celtis tala fo. obtusata, Celtis tala fo. subtomentosa, Celtis tala fo. subpilosa, Celtis tala fo. velutina, Celtis williamsii, and Momisia flexuosa) and second-step lectotypes for two names (Momisia chichape and Momisia crenata).